Comparison of Clinical Outcome in Surgically Treated Vs Conservatively Manged Rockwood Type III ACJ Dislocation - Ahmed, Hassaan; Suhail Amin, Major General (Indus Journal of Bioscience Research, 2025)
Background: Acromioclavicular joint (ACJ) dislocations are frequently encountered shoulder injuries, particularly in active individuals. The management of Rockwood Type III injuries remains contentious, with both surgical and conservative approaches being practiced. This study aims to prospectively compare clinical outcomes between the two modalities. Methods: A prospective comparative study was conducted at Combined Military Hospital (CMH), Rawalpindi, from January 2021- June 2023. A total of 140 patients with isolated Rockwood Type III ACJ dislocations were equally divided into two groups: Group A underwent surgical management (hook plate or TightRope fixation), and Group B received conservative treatment (immobilization and rehabilitation). Patients were followed at 2 weeks, 6 weeks, 3 months, and 6 months post-injury. Primary outcomes included Constant-Murley Score (CMS), Visual Analog Scale (VAS) for pain, radiological alignment, and complication rates. Results: At 6-month follow-up, Group A showed superior outcomes with a significantly higher mean CMS (88.4 ± 6.2 vs. 80.1 ± 7.5, p<0.001) and lower VAS pain scores (1.9 ± 1.1 vs. 3.4 ± 1.3, p<0.001). Radiological subluxation was less frequent in Group A (8.6%) than Group B (24.3%) (p=0.01). Return to pre-injury activity was faster in the surgical group (9.4 vs. 12.6 weeks). Complication rates were higher in Group A (12.9%) due to implant-related issues, compared to 5.7% in Group B. Conclusion: Surgical treatment for Rockwood Type III ACJ dislocations yields better short-term functional and anatomical outcomes compared to conservative management, albeit with a higher complication rate.